2021
DOI: 10.3390/ijms222111329
|View full text |Cite
|
Sign up to set email alerts
|

Two TGA Transcription Factor Members from Hyper-Susceptible Soybean Exhibiting Significant Basal Resistance to Soybean mosaic virus

Abstract: TGA transcription factors (TFs) exhibit basal resistance in Arabidopsis, but susceptibility to a pathogen attack in tomatoes; however, their roles in soybean (Glycine max) to Soybean mosaic virus (SMV) are unknown. In this study, 27 TGA genes were isolated from a SMV hyper-susceptible soybean NN1138-2, designated GmTGA1~GmTGA27, which were clustered into seven phylogenetic groups. The expression profiles of GmTGAs showed that the highly expressed genes were mainly in Groups I, II, and VII under non-induction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(72 reference statements)
2
5
0
Order By: Relevance
“…The results indicated that the StTGA family is conserved in the evolutionary history with the TGA TFs orthologs of other plants. This result corresponds well with previous observations in many plant species (Moon et al, 2018;Ullah et al, 2019;Jiang et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results indicated that the StTGA family is conserved in the evolutionary history with the TGA TFs orthologs of other plants. This result corresponds well with previous observations in many plant species (Moon et al, 2018;Ullah et al, 2019;Jiang et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…The expression heat map demonstrated that the TGA TFs may have played significant and complex roles in potato ( Figure 4 ), which was reflected in at least two aspects. First, the RNA-seq data-based heat map showed that the expression of most of the StTGAs was significantly different under abiotic/biotic stresses, which was consistent with previous studies ( Jiang et al, 2021 ). Second, the same gene showed different or even opposite expression patterns under different stresses or in different tissues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…TGA2 , TGA5 , and TGA6 make up Group II; they are connected and have functional redundancy. TGA3 and TGA7 make up Group III, TGA9 and TGA10 make up Group IV, and TGA8 is the solitary member of Group V. Among these identified TGAs , TGA1-TGA7 has been proven to interact with key resistance-related genes such as NPR1 , and participate in multiple signal regulation pathways in plants to improve plant biotic and abiotic stress resistance ( Johnson et al, 2001 ; Choi et al, 2004 ; Thurow et al, 2005 ; Jiang et al, 2021 ; Liu et al, 2022 ). In addition to Arabidopsis and tobacco, TGA has been identified in a variety of plants related to disease resistance, such as the TGA gene in soybean responds to mosaic virus, kiwifruit TGAs plays a role in the process of Pseudomonas syringae pv.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Arabidopsis and tobacco, TGA has been identified in a variety of plants related to disease resistance, such as the TGA gene in soybean responds to mosaic virus, kiwifruit TGAs plays a role in the process of Pseudomonas syringae pv. Actinidiae ( Psa ) infection ( Jiang et al, 2021 ; Liu et al, 2022 ). In Brachypodium distachyon , the TGA -promoted transcription of SA-inducible PR1 is orchestrated by the activator BdNPR2 and the repressor BdNPR1 to enforce immune resistance ( Shimizu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%